1998
DOI: 10.1161/01.atv.18.5.732
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Thyroid Function on LDL Oxidation

Abstract: Abstract-In this study, the effect of different levels of thyroid hormone and metabolic activity on low density lipoprotein (LDL) oxidation was investigated. Thus, in 16 patients with hyperthyroidism, 16 with hypothyroidism, and 16 age-and sex-matched healthy normolipidemic control subjects, the native LDL content in lipid peroxides, vitamin E, ␤-carotene, and lycopene, as well as the susceptibility of these particles to undergo lipid peroxidation, was assessed. Hyperthyroidism was associated with significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
78
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(87 citation statements)
references
References 41 publications
7
78
0
Order By: Relevance
“…Although adjustment for s-albumin (one of the main transporters of T3 in plasma) did not modify the observed associations, we should acknowledge that fT3 is not tantamount to T3. Several studies have, nevertheless, suggested anti-atherosclerotic effects of fT3 on the vascular bed via its effect on mitochondrial oxidative systems, induction of vasodilatory molecules, inhibition of angiotensin II receptor expression and inhibition of downstream signal transduction, mechanisms all of which do not necessarily involve the inflammatory cascade (26)(27)(28).…”
Section: Discussionmentioning
confidence: 99%
“…Although adjustment for s-albumin (one of the main transporters of T3 in plasma) did not modify the observed associations, we should acknowledge that fT3 is not tantamount to T3. Several studies have, nevertheless, suggested anti-atherosclerotic effects of fT3 on the vascular bed via its effect on mitochondrial oxidative systems, induction of vasodilatory molecules, inhibition of angiotensin II receptor expression and inhibition of downstream signal transduction, mechanisms all of which do not necessarily involve the inflammatory cascade (26)(27)(28).…”
Section: Discussionmentioning
confidence: 99%
“…The organic chain-breaking antioxidant potential of plasma appeared to be rather low and decreased in hypothyroidism. Such conditions may be in part caused by the low plasma primary chain-breaking antioxidant -α-tocopherol -content observed concomitantly with hypothyroid state (Constantini et al, 1998;Shinohara et al, 2000). Although the blood plasma of euthyroid rabbits possesses very high inorganic iron-binding, iron-oxidising and scavenging activities (from 77.1% to 86.9% of oxygen radicals inhibition), no alteration in these activities were noticed in hypothyroid rabbits.…”
Section: Discussionmentioning
confidence: 99%
“…Pamplona et al (1999) suggest that thyroid hormones acting as physiologic modulators of tissue oxidative stress and protein degradation are more effective in cytosol, whereas DNA is more protected from oxidative damage. In humans, the low density lipoprotein (LDH) oxidation was shown to be significantly lower in hypothyroid than in hyperthyroid subjects (Constantini et al, 1998).…”
Section: Acta Veterinaria Hungarica 51 2003mentioning
confidence: 99%
“…6,7,8 dyslipidemia But in patients with overt hypothyroidism, activity of HMG-CoA reductase tends to decrease while TC 9,10 and LDL-C levels are increased. This can be explained as increased thyroid hormones leads to decresedcatabolism of 11,12 LDL and IDL Hyperthyroidism canalso be the contributory factor that may cause unexpected improvement of lipid profile 13 in hyperlipidemic patients Since, hyperthyroidism whether overt or subclinical , there is decrease in LDLand HDL cholesterol resulting enhanced oxidation of LDL that depends 14 on level of FT4. Decrease in HDL-C levels is associated with increased CETP-mediated transfer of cholesteryl esters from HDL to VLDL and increased HL-mediated catabolism of 15,16 HDL .…”
Section: Discussionmentioning
confidence: 99%